2021
DOI: 10.1126/sciimmunol.abg4176
|View full text |Cite
|
Sign up to set email alerts
|

CD36 family members are TCR-independent ligands for CD1 antigen–presenting molecules

Abstract: CD1c presents lipid-based antigens to CD1c-restricted T cells, which are thought to be a major component of the human T cell pool. However, the study of CD1c-restricted T cells is hampered by the presence of an abundantly expressed, non–T cell receptor (TCR) ligand for CD1c on blood cells, confounding analysis of TCR-mediated CD1c tetramer staining. Here, we identified the CD36 family (CD36, SR-B1, and LIMP-2) as ligands for CD1c, CD1b, and CD1d proteins and showed that CD36 is the receptor responsible for non… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Our data further support a CD1d-CD36 axis by which CD1d could in turn modulate the internalization of CD36 and consequently control lipid uptake. It is worth noting that a similar function could be also relevant to other CD1 family members expressed in human cells, such as CD1b or CD1c, as tetramers from these molecules have also been shown to bind CD36 in human monocytes 28 . CD1d molecules have a short intracellular tail which has been shown to control their intracellular trafficking and rate of internalization in steady state 38,39 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Our data further support a CD1d-CD36 axis by which CD1d could in turn modulate the internalization of CD36 and consequently control lipid uptake. It is worth noting that a similar function could be also relevant to other CD1 family members expressed in human cells, such as CD1b or CD1c, as tetramers from these molecules have also been shown to bind CD36 in human monocytes 28 . CD1d molecules have a short intracellular tail which has been shown to control their intracellular trafficking and rate of internalization in steady state 38,39 .…”
Section: Discussionmentioning
confidence: 92%
“…In line with this, other surface molecules -such as CD146-have been shown to modulate CD36 internalization during lipid uptake ultimately controlling macrophage activation 35 . Interestingly, a recent technical report has identified CD36 as a ligand for human CD1 tetramers 28 . While the physiological relevance of this observation remains unexplored, the authors suggest that CD36 could play a role in the pathways of lipid loading into CD1 molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human T-cell lines were stained with tetramers at 2 μg/ml in PBS containing 1% BSA and 0.01% sodium azide. Cells were preincubated with unlabeled CD36 antibody (5-271; Biolegend) for 10 min at RT ( 37 ). Tetramer was added and incubated for 10 min at RT in the dark, followed by addition of cell surface antibodies for 10 min at RT.…”
Section: Experimental Prodecuresmentioning
confidence: 99%
“…Immunofluorescence assays of tissue sections showed that BTK was mainly located in macrophages at the junction of cancer nest and stroma, and negatively correlated with the abundance of NK cells (Supplementary Figures 9C,D), suggesting that BTK promotes tumor progression by promoting local immunosuppression. As a specific marker of dendritic cells, Cd1c has the function of regulating antigen presentation of dendritic cells and improving TME (Yuan et al, 2019;Gherardin et al, 2021). We found that both mRNA and protein expression of Cd1c were down-regulated in LUAD tumor tissues (Supplementary Figures 4, 5), while the down-regulation of Cd1c was associated with poor survival (Supplementary Figure 4).…”
Section: Discussionmentioning
confidence: 82%